Integrating Screen Time Monitoring and Visual Health Interventions Using a Web-Based Application for Children’s Digital Well-Being - Mhrez, Amani; Mohamed Elbeshti,; Houida Alfoghi,; Laila Alkabash, (AlQalam Journal of Medical and Applied Sciences, 2026)
Today, children are increasingly exposed to digital devices for educational, entertainment, and social purposes. Although these technologies provide significant benefits, prolonged and uninterrupted screen time has been linked to adverse visual outcomes, including digital eye strain, reduced blink rate, ocular fatigue, and potential long-term effects on visual development. This study presents a web-based system designed to actively promote children's digital eye health by integrating continuous screen time monitoring with algorithm-driven visual break reminders and guided eye exercises. Unlike traditional applications that only record screen usage or provide parental controls, the proposed system provides interactive interventions directly in the user experience. The study involved sixty children aged six to twelve who were monitored over four weeks, with metrics including screen time, adherence to recommended visual breaks, and adherence to guided eye exercises. The results showed significant improvements in adherence to the visual break schedule and exercise completion rate. The proposed system demonstrates how web-based technologies can be leveraged to translate preventive visual health guidelines into practical, engaging interventions that promote healthy digital behaviors among children.